Exploring Social Media Engagement, Narrative Identity Construction, and Emerging Forms of Social Activism in Nigeria - Oloruntoba Oyedele (International Journal of Social Science and Religion (IJSSR), 2026)
This study examines how digital media shapes urban Nigerian youth's engagement with popular culture, identity construction, and social activism. With the rapid expansion of social media, young people are increasingly using these platforms to perform their identities and engage in civic matters. The research, using qualitative methods including semi-structured interviews and thematic content analysis, found that 78% of participants actively participate in online activism, while 85% reported that social media significantly shapes their self-concept and cultural identity. Key themes identified were identity performance, peer influence, and digital civic participation. The findings highlight the role of social media not only in cultural expression but also in mobilizing youth around social issues. This research emphasizes the need for digital literacy, cultural understanding, and strong policy support to maximize the positive potential of online engagement in shaping youth identity and activism. The novelty of the study lies in its focus on the intersection of digital culture and social activism among urban Nigerian youth, offering insights into how digital spaces transform personal and collective identities.